Potensi Resistensi Virus HIV-1 terhadap Terapi Anti Retroviral (ART) pada Pasien Voluntary Counseling and Testing (VCT) di Beberapa Kota di Indonesia - Hariastuti, Nur Ika; Wibowo, Holy Arif; Adam, Kindi; Subangkit, nFN; Kipuw, Natalie Laurensia; Roselinda, nFN (Media Penelitian dan Pengembangan Kesehatan, 2016)
Human Immunodeficiency Virus (HIV) is a virus that damages the immune system. The use of antiretroviraltherapy drugs combination (ARV) has demonstrated highly effective in controlling thedevelopment of the HIV virus and prolongs survival. Comprehensive coverage of antiretroviral therapy(ART) also has an impact on the incidence of mutations in the HIV virus that can lead to resistance. Ingeneral, resistance to a particular drug is the result of a mutation in a number of positions in the proteincodinggenes that are targeted by drugs. This study is aimed to find out mutations that related to ARVresistance in some cities in Indonesia. Genotypic assays are used in this study to analyze the viralresistance properties. The samples are from stored biological materials in the Center for Biomedicaland Basic Technology of Health. One hundred and eightspecimens that meet the inclusion criteriawere amplified and sequenced. Further analysis is conducted by uploading sequences to the StanfordUniversity website for the analysis of resistance mutations. Based on the results of this study there aresome mutations in the HIV virus that leads to a low potential of antiretroviral drug resistance of efavirenz(EFV) and nevirapine (NVP). These drugs are used in the first-line treatment of HIV in Indonesia.Overview of the mutations that cause viral resistance to antiretroviral drugs with genetic methods isexpected to serve as baseline data for program development of new drugs or vaccines HIV / AIDS inthe response to HIV in Indonesia.Keywords: resistance, HIV-1 virus, VCTÂ AbstrakHuman Immunodeficiency Virus (HIV) adalah virus yang merusak sistem kekebalan tubuh. Penggunaankombinasi obat terapi anti retroviral (ARV) telah menunjukkan efektivitas yang tinggi dalammengendalikan perkembangan virus HIV dan memperpanjang harapan hidup penderita. Cakupan pemberian anti retroviral therapy (ART) yang luas juga berdampak pada timbulnya mutasi pada virus HIV sehingga dapat menyebabkan resistensi. Secara umum, resistensi terhadap obat tertentu adalah hasildari mutasi pada sejumlah posisi dalam gen pengkode protein yang ditargetkan oleh obat. Penelitianini bertujuan untuk mengetahui adanya mutasi yang mengarah pada resistensi terhadap ART pada beberapa kota di Indonesia. Metode yang digunakan untuk melakukan analisis resistensi pada studiini adalah dengan pemeriksaan genotipik. Sampel yang digunakan adalah Bahan Biologi Tersimpanpada Pusat Biomedis dan Teknologi Dasar Kesehatan. Seratus delapan spesimen yang memenuhi kriteria inklusi diamplifikasi dan dilakukan sequencing. Selanjutnya analisis hasil sekuensing virus HIV dilakukan dengan mengunggah sekuen ke situs web Stanford University untuk analisis mutasi resistensi.Berdasarkan hasil penelitian ini ditemukan adanya mutasi pada virus HIV yang mengarah pada lowpotential resistensi obat ARV yaitu jenis efavirenz (EFV) dan nevirapine (NVP). Obat ini merupakan linipertama pengobatan HIV di Indonesia. Tinjauan mengenai mutasi yang menyebabkan resistensi virusterhadap ARV dengan metode genetik ini diharapkan dapat dijadikan sebagai data dasar bagi programpengembangan obat baru atau vaksin HIV/AIDS dalam program penanggulangan HIV di Indonesia.Kata Kunci: resistensi, virus HIV-1, VCT